Ultrastructure of fibrils in developing human and guinea-pig tympanic membrane. - McMinn, R M (1978)
The development of connective tissue of the tympanic membrane has been examined in guinea-pig embryos and fetuses from 22 days of gestation (10 mm CR length) to birth (at about 67 days, 100 mm), in neonatal animals for the first 3 weeks of life, and in human embryos and fetuses aged 6, 11, 15 and 22 weeks. In the guinea-pig up to 34 days of gestation there was little evidence of fibril formation, but from 37 days onwards fibrils were an obvious feature of the tympanic membrane area. When first observed they resembled small collagen fibrils but there was no cross-banding, and within a week to 10 days they showed the foursubunit configuration typical of adult tympanic membrane fibrils in this species. There was no increase in fibril diameter and elastic fibres were not seen. In the human fetuses small groups of collagen fibrils (already of larger diameter than guinea-pig fibrils) were apparent at 11 weeks, together with small groups of elastic microfibrils. Later specimens showed increasing numbers of cross-banded collagen fibrils and the development of the amorphous elastin component in association with the microfibrils.